Influence of desensitizing and anti-erosive toothpastes on dentine permeability: An in vitro study - João-Souza, Samira Helena (2019)
Objective: This study analyzed the effect of desensitizing and/or anti-erosive toothpastes on dentine permeability. Methods: One-mm dentin discs were prepared from human molars and exposed to EDTA solution (5 min, 17%). Initial dentine permeability was measured, under constant pressure. Specimens were randomly allocated into 10 groups: four anti-erosive toothpastes (calcium silicate + sodium phosphate, potassium nitrate, stannous chloride + chitosan, oligopeptide-104); four desensitizing toothpastes (arginine + calcium carbonate, calcium sodium phosphosilicate, strontium acetate, stannous fluoride); and two controls (regular fluoridated toothpaste, and human saliva). They were submitted to a 5-day erosion-abrasion cycling model. Erosion consisted of immersion in citric acid (2 min, 0.3%, natural pH ˜ 2.6, 4x/day), followed by 1 h exposure to human saliva. Specimens were brushed for 15 s (2 N, 45 strokes) with the toothpaste slurries (total exposure time of 2 min). After 5 cycles, the final dentine permeability was determined. Dentine permeability change was calculated as a percentage of the initial hydraulic conductance (%Lp). Data were analyzed with one-way ANOVA and Tukey tests (α=0.05). Results: The toothpastes calcium silicate + sodium phosphate and potassium nitrate, showed significant decrease in %Lp, with no difference between them. The regular fluoridated toothpaste also decreased the %Lp, not differing from potassium nitrate. No desensitizing toothpaste showed change in %Lp. Human saliva, oligopeptide-104 and stannous chloride + chitosan presented significant increase in %Lp, without difference between them. Conclusion: Calcium silicate + sodium phosphate, potassium nitrate, and the regular fluoridated toothpaste decreased dentine permeability, whereas the desensitizing toothpastes tested did not. Clinical relevance: Toothpastes had distinct impacts on dentine permeability, which may reflect a variable effect on the treatment of dentine hypersensitivity. Within the limitations of a laboratory-based study, toothpastes with an anti-erosive claim could also be effective in reducing the pain in dentine hypersensitivity.